2019
DOI: 10.1007/s11356-019-04453-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mineral forms of nitrogen and sulfur and enzymatic activities during composting of lignocellulosic waste and chicken feathers

Abstract: The aim of this study was to show the dynamics of changes in the activity of enzymes responsible for C, N, and S metabolism, i.e., cellulase, protease, urease, and arylsulfatase in two lignocellulosic composts as well as changes in the concentration of mineral forms important in plant nutrition (N-NH 4 + , N-NO 3 − , S-SO 4 2− ). Most of the enzyme activity was higher during 10 weeks of composting in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The final values of the urease activity across various regardless of the considerable difference in initial N contents and enzyme ac plies that urease activity is a promising indicator of maturity. Similar resu that measuring enzymatic activity and organic matter decomposition can formation about compost maturity [52]…”
Section: Microbial Activity and Enzyme Propertymentioning
confidence: 89%
“…The final values of the urease activity across various regardless of the considerable difference in initial N contents and enzyme ac plies that urease activity is a promising indicator of maturity. Similar resu that measuring enzymatic activity and organic matter decomposition can formation about compost maturity [52]…”
Section: Microbial Activity and Enzyme Propertymentioning
confidence: 89%
“…Nitrogen losses are possible, either by nitrate leaching in the case of unprotected composts piles under rainy season, or by volatilization of ammonia (NH3), and nitrous oxide (N2O). Bohacz, J. (2019) found that NH3 volatilization was intensified under alkaline conditions of the composted biomass.…”
Section: Nitrogen Forms and Concentrations In Heaps During Compostingmentioning
confidence: 99%
“…In the thermophilic stage, the change rate in NH4 + -N correlated to total N was negative but was positively correlated to NO3 --N in all heaps, proving that any decrease in total nitrogen during composting was accompanied by rise in NH4 + formation followed by rise in NO3formation too. Nitrogen metabolism was associated with ammonia volatilization as a result of ammonification activities by microorganisms from the beginning of the composting process as stated by Bohacz, J. (2019).…”
Section: Nitrogen Forms and Concentrations In Heaps During Compostingmentioning
confidence: 99%
“…Co-composting with herbal wastes tends to increase the rate of organic matter (OM) degradation by microorganisms and it often results in improved compost quality with high antipathogenic properties (Zhou et al 2016 , 2018 ). However, the use of herbal residues may at times negatively influence the composting process because an increased lignocellulose content and the remaining secondary metabolites can inhibit nutrient cycling, litter decomposition, and seed germination (Bohacz 2019a ; De Martino et al 2010 ; Guénon et al 2017 ; Shang et al 2016 ; Zhang et al 2019 ). Inoculation of the waste material with specific microbial cultures may stimulate the biological degradation of OM, thus improving final compost quality (Huang et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%